Analysis of maternal and foetal outcome of post-dated pregnancy in a tertiary care centre - G., Ramadevi; C. H., Sailaja; C. H., Madhuri; Y., Anuragamayi; Ryali, Sujatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Managing pregnancy with post-dates is becoming a challenging issue due to increasing fetal morbidity and mortality. The study aimed to analyse the maternal and fetal outcomes of post-term pregnancies among Indian women, considering their earlier fetal maturation. Conducted over 18 months with 100 cases, the prospective observational study focused on pregnant mothers at or beyond 40 weeks gestational age, excluding those with certain medical complications. Methods: After obtaining approval from the ethics committee and informed consent from eligible participants, detailed histories and examinations were conducted, with close monitoring until delivery and postnatal care. Inclusive criteria encompassed singleton pregnancies with cephalic presentation, while exclusions included non-cephalic presentation, congenital anomalies, and various medical complications. Results: Revealed a predominance of primigravida women aged 20 to 35 years at 40 to 40 weeks and 6 days gestation. Spontaneous delivery occurred in 58%, with 90% delivering vaginally, while all multigravida births were vaginal post-induction. Cesarean sections were performed in 14%, primarily due to failed induction followed by fetal distress. Meconium-stained liquor was most prevalent at 42 weeks or later, correlating with higher perinatal mortality and NICU admissions in infants born beyond 42 weeks. Conclusions: Vigilant monitoring proved crucial in averting fetal jeopardy, emphasizing the importance of timely interventions to mitigate complications associated with post-term pregnancies. This study sheds light on the unique considerations and outcomes of post-dated pregnancies in the Indian population, contributing valuable insights for maternal and neonatal care in similar settings.